The priorities and guidelines for the use of CSDP framework, as deriving from the EU Global Strategy - Πετρόπουλος, Βασίλειος (Πανεπιστήμιο Πελοποννήσου, 2016)
The release of the EU Global Strategy (2016) incorporates the CSDP framework as one of the available means the EU can use to achieve its goals on security. The existence of such a comprehensive strategy can provide, under the proper analysis, indications as to the priorities and guidelines for the use of CSDP framework in the coming period. The demand for the use of CSDP framework is expected to grow and the EU Global Strategy is a catalyst for action. The analysis did provide some useful indications as to the EU’s willingness to enhance common defence, the regional and thematic priorities for CSDP action, and the guidelines as to the nature and extent of CSDP missions. The formation and implementation of a tailor made CSDP strategy will eventually determine the course of CSDP framework and could bestow upon the CSDP framework the strategic perspective or not.
Οι προτεραιότητες και οι κατευθύνσεις για την χρήση του πλαισίου της ΚΠΑΑ, όπως απορρέουν από την Παγκόσμια Στρατηγική της Ε.Ε
Keywords: Ασφάλεια, Διεθνής; Άμυνα; Παγκόσμια πολιτική; Στρατηγική; Ασφάλεια; Άμυνα; Ευρωπαϊκή Ένωση; ΚΠΑΑ; Πολιτική